2011
DOI: 10.1371/journal.pone.0022187
|View full text |Cite
|
Sign up to set email alerts
|

Network Neighbors of Drug Targets Contribute to Drug Side-Effect Similarity

Abstract: In pharmacology, it is essential to identify the molecular mechanisms of drug action in order to understand adverse side effects. These adverse side effects have been used to infer whether two drugs share a target protein. However, side-effect similarity of drugs could also be caused by their target proteins being close in a molecular network, which as such could cause similar downstream effects. In this study, we investigated the proportion of side-effect similarities that is due to targets that are close in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
68
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 44 publications
(61 reference statements)
2
68
0
Order By: Relevance
“…We might identify key molecules within PRN structure (integrators or otherwise) that facilitate or constrain evolutionary change. Such approaches are being used in pharmacology to identify key targets for drug discovery [51] and their potential side-effects [52]. An ecological example would be to ask what bird lineages were able to successfully diversify from tropical habitat into temperate.…”
Section: How To Study Prnsmentioning
confidence: 99%
“…We might identify key molecules within PRN structure (integrators or otherwise) that facilitate or constrain evolutionary change. Such approaches are being used in pharmacology to identify key targets for drug discovery [51] and their potential side-effects [52]. An ecological example would be to ask what bird lineages were able to successfully diversify from tropical habitat into temperate.…”
Section: How To Study Prnsmentioning
confidence: 99%
“…Drugs often interact with a number of additional proteins beyond their primary targets (1)(2)(3). Therefore, drugs have effects on multiple pathways beyond altering the activity of a single protein.…”
mentioning
confidence: 99%
“…Therefore, drugs have effects on multiple pathways beyond altering the activity of a single protein. Two histone deacetylase (HDAC) 1 inhibitors approved by the U.S. Food and Drug Administration, suberoylanilide hydroxamic acid (SAHA) and depsipeptide (Romidepsin), are used for the treatment of advanced and refractory cutaneous T-cell lymphoma in patients with progressive, persistent, or recurrent disease (4). SAHA has the permeability to cross the blood-brain barrier and cause biological responses in the mouse brain, making it a preferred candidate drug for testing in the central nervous system (5,6).…”
mentioning
confidence: 99%
“…Recently, Brouwers et al (2011) investigated how side effect similarities of targets depend on their closeness in the human PIN. They found that a certain number of pairs of two drugs without common targets show similar side effects, when they are close in the human PIN.…”
Section: Predicting Candidate Drug Targets and Their Side Effects Basmentioning
confidence: 99%
“…With recent influx of information of biological networks, especially the human interactome, analyses like Brouwers et al (2011) or Wang et al (2011 can be refined and adapted to infer still unknown adverse side effects of drugs and to predict possible target genes. Indeed, by integrating information of the human PIN with similarities between two genes (e.g., GO semantic and sequence similarity) and those between two drugs (e.g., chemical and drug therapeutic similarity), several recent researches attempted to develop a method to predict possible targets for therapeutic drugs (Zhao & Li 2010, Perlman et al 2011).…”
Section: Predicting Candidate Drug Targets and Their Side Effects Basmentioning
confidence: 99%